1876-77 N.C. Sess. Laws 606 - (:unkn) unknown (My University, 1877)
Resolution of Mar. 6, 1877, N.C. Pub. Laws 606 (Resolution in Relation to Public Arms): That the adjutant general be required to collect and deposit in the state arsenal, such arms and equipments belonging to the state as are now in unauthorized hands, whereever they may be found, and that the necessary expenses of travel, freight and drayage, incident thereto, be paid by the treasurer of the state upon the warrant of the governor.
Keywords: ARMED FORCES